Comeback of epitaxial graphene for electronics: large-area growth of bilayer-free graphene on SiC. (27th September 2016) - Kruskopf, Mattias; Pakdehi, Davood Momeni; Pierz, Klaus; Wundrack, Stefan; Stosch, Rainer; Dziomba, Thorsten; Götz, Martin; Baringhaus, Jens; Aprojanz, Johannes; Tegenkamp, Christoph; Lidzba, Jakob; Seyller, Thomas; et al.
Abstract: We present a new fabrication method for epitaxial graphene on SiC which enables the growth of ultra-smooth defect- and bilayer-free graphene sheets with an unprecedented reproducibility, a necessary prerequisite for wafer-scale fabrication of high quality graphene-based electronic devices. The inherent but unfavorable formation of high SiC surface terrace steps during high temperature sublimation growth is suppressed by rapid formation of the graphene buffer layer which stabilizes the SiC surface. The enhanced nucleation is enforced by decomposition of deposited polymer adsorbate which acts as a carbon source. Unique to this method are the conservation of mainly 0.25 and 0.5 nm high surface steps and the formation of bilayer-free graphene on an area only limited by the size of the sample. This makes the polymer-assisted sublimation growth technique a promising method for commercial wafer scale epitaxial graphene fabrication. The extraordinary electronic quality is evidenced by quantum resistance metrology at 4.2 K showing ultra-high precision and high electron mobility on mm scale devices comparable to state-of-the-art graphene.